2014
DOI: 10.1152/ajpheart.00744.2013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol treatment rescues neurovascular coupling in aged mice: role of improved cerebromicrovascular endothelial function and downregulation of NADPH oxidase

Abstract: Moment-to-moment adjustment of cerebral blood flow (CBF) to neuronal activity via neurovascular coupling is essential for the maintenance of normal neuronal function. Increased oxidative stress that occurs with aging was shown to impair neurovascular coupling, which likely contributes to a significant age-related decline in higher cortical function, increasing the risk for vascular cognitive impairment. Resveratrol is a polyphenolic compound that exerts significant antiaging protective effects in large vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
251
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 177 publications
(271 citation statements)
references
References 53 publications
18
251
0
2
Order By: Relevance
“…1B), indicating that IGF‐1 deficiency leads to neurovascular uncoupling, mimicking the aging phenotype (Toth et al ., 2014a). IGF‐1 deficiency could reduce functional hyperemia by impairing neural activity evoked by whisker stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1B), indicating that IGF‐1 deficiency leads to neurovascular uncoupling, mimicking the aging phenotype (Toth et al ., 2014a). IGF‐1 deficiency could reduce functional hyperemia by impairing neural activity evoked by whisker stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…ACh‐induced CBF responses were significantly attenuated in IGF‐1‐deficient mice (Fig. 2B), supporting the concept that IGF‐1 deficiency impairs cerebromicrovascular endothelial function, mimicking the aging phenotype (Toth et al ., 2014a). Previously, it has been found that in models of vascular aging in the periphery, IGF‐1 decreases vascular oxidative stress and improves endothelial function (Ungvari & Csiszar, 2012), whereas it does not significantly affect endothelium‐independent vasodilation elicited by NO donors (Bailey‐Downs et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations